Lithium ion conductive solid electrolyte and all-solid-state battery
By introducing monoclinic crystal structures of lithium, tantalum, boron, phosphorus and oxygen into the lithium-ion conductive solid electrolyte, the problems of unstable humidity of sulfide-based electrolytes and low conductivity of oxide-based electrolytes are solved, and high ion conductivity is achieved , and thermal stability, suitable for a variety of lithium-ion battery applications.
Patent Information
- Application Number
- CN202180084251.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-12-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-12-23
AI Technical Summary
The sulfide-based solid electrolyte has a problem of humidity instability, while the oxide-based solid electrolyte has a low ion conductivity, making it difficult to meet the needs of high ion conductivity and thermal stability.
Lithium-ion conductive solid electrolyte with a monoclinic crystal structure is adopted, containing lithium, tantalum, boron, phosphorus and oxygen as constituent elements, and its thermal stability and chemical stability are improved through specific crystal structures and element content ratios. Achieve high ion conductivity under low temperature conditions.
It achieves high ion conductivity and thermal stability, and is suitable for all-solid lithium-ion batteries, lithium-air batteries and other applications. It has a simple manufacturing method and can be sintered at low temperatures to reduce the impact on other substrates.
Smart Images

Figure CN116601113B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a novel solid electrolyte and an all-solid-state battery having excellent lithium ion conductivity. Background Art
[0002] Rechargeable secondary lithium-ion batteries are used in a variety of applications, from portable electronic devices to batteries for electric vehicles. However, commercial lithium-ion batteries have significant safety issues in using flammable organic liquid electrolytes with low thermal stability. In addition, there is a problem of short-circuiting lithium-ion batteries when lithium dendrites grow in organic electrolytes.
[0003] In order to solve the problem of organic liquid electrolytes, a lot of research has been done on solid electrolyte materials. As a non-volatile and thermally stable solid electrolyte, it can replace organic liquid electrolytes and greatly improve safety. Solid lithium-ion electrolytes with high ion conductivity and excellent mechanical strength have been used in lithium-air batteries, lithium-based redox flow batteries, Li-H2O2 semi-fuel cells, chemical sensors, etc.
[0004] Therefore, oxide-based solid electrolytes and sulfide-based solid electrolytes containing lithium have been widely studied. Sulfide-based solid electrolytes have lithium ion conductivity that is equal to or higher than that of conventional liquid electrolytes. On the other hand, oxide-based solid electrolytes are relatively superior in terms of ease of handling, mechanical properties, chemical properties, and thermal stability.
[0005] For example, as a sulfide-based solid electrolyte, Patent Document 1 (Japanese Patent Publication No. 2020-173992) discloses a method for producing a sulfide solid electrolyte, which comprises mixing a raw material composition containing constituent components of a sulfide with tetrahydrofuran to obtain a precursor, and then calcining the mixture to volatilize the tetrahydrofuran, wherein the sulfide contains Li element, P element, and S element.
[0006] In addition, as an oxide-based solid electrolyte, Non-Patent Document 1 describes that LiTa2PO8 having a monoclinic crystal structure exhibits high lithium ion conductivity (total conductivity (25°C): 2.5×10 -4 S cm -1 ).
[0007] In addition, Patent Document 2 discloses a solid electrolyte and an all-solid-state battery that can achieve high ion conductivity even when sintered at low temperatures, and discloses that the solid electrolyte contains a lithium ion conductive material having a garnet-type structure, a lithium ion conductive material having a LISICON-type structure, and a compound containing Li and B.
[0008] In addition, Patent Document 3 discloses an ion-conducting solid electrolyte compound, wherein the LiTa2PO8 produced in Example 1 is a monoclinic crystal having an a-axis length of The length of the b axis is The length of the c-axis is And the lattice constant of the axis angle β is 90.04°.
[0009] Prior art literature
[0010] Non-patent literature
[0011] Non-patent document 1: J. Kim et al., J. Mater. Chem. A, 2018, 6, p22478-22482
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2020-173992
[0014] Patent Document 2: International Publication No. 2019 / 044901
[0015] Patent Document 3: International Publication No. 2020 / 036290 Summary of the invention
[0016] However, sulfide-based solid electrolyte compounds are generally unstable in humidity. In addition, oxide-based solid electrolytes have relatively good processability, mechanical properties, chemical properties, and thermal stability, but their ion conductivity is relatively low and needs to be further improved.
[0017] Therefore, an object of the present invention is to provide a novel solid electrolyte having excellent ion conductivity.
[0018] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved according to the following configuration examples, thereby completing the present invention.
[0019] The configuration examples of the present invention are as follows.
[0020] [1] A lithium ion conductive solid electrolyte comprising a chalcogenide,
[0021] The chalcogenide has a monoclinic crystal structure, and
[0022] The a-axis length of the monoclinic crystal is The length of the b axis is The length of the c-axis is And the axis angle β is in the range of 90.01 to 90.08°.
[0023] [2] The lithium ion conductive solid electrolyte according to [1], wherein the chalcogenide has lithium, tantalum, boron, phosphorus, and oxygen as constituent elements.
[0024] [3] The lithium ion conductive solid electrolyte according to [1] or [2], wherein the monoclinic crystal structure is composed of lithium, tantalum, phosphorus, and oxygen as constituent elements.
[0025] [4] The lithium ion conductive solid electrolyte according to any one of [1] to [3], wherein the unit cell volume of the monoclinic crystal is
[0026] [5] The lithium ion conductive solid electrolyte according to any one of [1] to [4], wherein the boron content is 0.10 to 5.00 atomic %.
[0027] [6] The lithium ion conductive solid electrolyte according to any one of [1] to [5], wherein the tantalum content is 10.00 to 17.00 atomic %.
[0028] [7] The lithium ion conductive solid electrolyte according to any one of [1] to [6], wherein the phosphorus content is 5.00 to 8.50 atomic %.
[0029] [8] The lithium ion conductive solid electrolyte according to any one of [1] to [7], wherein the lithium content is 5.00 to 20.00 atomic %.
[0030] [9] The lithium ion conductive solid electrolyte according to any one of [1] to [8], further comprising niobium, wherein the niobium content is 0.10 to 5.00 atomic %.
[0031]
[10] The lithium ion conductive solid electrolyte according to any one of [1] to [9], wherein the content of the monoclinic crystal is 70.0% or more.
[0032]
[11] The lithium ion conductive solid electrolyte according to any one of [1] to
[10] , further comprising silicon, wherein the upper limit of the silicon content is 0.15 atomic %.
[0033]
[12] The lithium ion conductive solid electrolyte according to any one of [2] to
[11] , wherein boron exists at the grain boundaries.
[0034]
[13] An all-solid-state battery comprising:
[0035] A positive electrode having a positive active material,
[0036] A negative electrode having a negative electrode active material, and
[0037] A solid electrolyte layer between the positive electrode and the negative electrode,
[0038] The solid electrolyte layer includes the lithium ion conductive solid electrolyte described in any one of [1] to
[12] .
[0039]
[14] According to the all-solid-state battery described in
[13] , the positive electrode active material contains LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1 and 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O 12 One or more compounds.
[0040]
[15] According to the all-solid-state battery described in
[13] or
[14] , the negative electrode active material contains LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1 and 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8(PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4[M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0 and 0≤y9≤0.6, a9 is the average valence of M9, b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi and graphite.
[0041]
[16] The all-solid-state battery according to any one of
[13] to
[15] , wherein the positive electrode and the negative electrode contain the lithium ion conductive solid electrolyte according to any one of [1] to
[12] .
[0042] According to the present invention, a lithium ion conductive solid electrolyte composed of a single crystal having a predetermined crystal structure is provided. The solid electrolyte has excellent thermal stability and chemical stability and high ion conductivity. This solid electrolyte can be used in ion conductive electrolyte materials such as all-solid lithium ion batteries, lithium-air batteries (Li-Air battery), lithium redox flow batteries (Li-redox flowbattery), Li-H2O2 semi-fuel cells, chemical sensors, etc.
[0043] In addition, the manufacturing method of the lithium ion conductive solid electrolyte of the present invention is simple, and for example, a fully solid battery can be easily produced by stacking and sintering with the positive electrode material or the negative electrode material while suppressing the decomposition and deterioration of the active material contained in the positive electrode active material layer and the negative electrode active material layer. In addition, according to the present invention, low-temperature sintering can be performed, so miniaturization can be achieved, and the impact on other substrates can also be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 3 and 1 are XRD patterns of the solid electrolytes obtained in Example 3 and Comparative Example 1.
[0045] Figure 2 These are a secondary electron image and a boron mapping image of the solid electrolyte obtained in Example 3 obtained by EPMA. DETAILED DESCRIPTION
[0046] Lithium-ion conductive solid electrolytes
[0047] A lithium ion conductive solid electrolyte (hereinafter also referred to as the present solid electrolyte) according to one embodiment of the present invention comprises a chalcogenide and has a monoclinic crystal structure, wherein the a-axis length of the monoclinic crystal is The length of the b axis is The length of the c-axis is Furthermore, the axis angle β is in the range of 90.01 to 90.08°, and the solid electrolyte has lithium ion conductivity.
[0048] By including a monoclinic crystal having such a crystal structure, a lithium ion conductive solid electrolyte having better lithium ion conductivity than conventional lithium ion conductive solid electrolytes can be provided.
[0049] The crystal structure of the monoclinic crystal, the a-axis length, b-axis length, c-axis length and axis angle β of the monoclinic crystal can be confirmed by morphological observation using SEM-EDX, chemical analysis, X-ray diffraction, and the like, and the composition and crystal structure thereof.
[0050] The shape of the solid electrolyte is not particularly limited, and may be granular, that is, powdery, in the form of pellets, sheets, or the like, or in the form of an amorphous block, and may be appropriately selected depending on the form of use.
[0051] Chalcogenides in this specification are compounds of chalcogen elements and elements with lower electronegativity than chalcogen elements, and are oxides, sulfides, etc. There are no particular limitations on the chalcogenides as long as they can form a monoclinic crystal having the above characteristics, but in the present invention, substances containing oxygen are preferred.
[0052] In the present invention, the chalcogenide has a stoichiometric formula of the following general formula (1).
[0053] A x (M a T b G c K d ) y (1)
[0054] In the chemical formula 1, A is an element constituting a cation having an oxidation state of +1, M is an element constituting a cation having an oxidation state of +4, +5 or +6, T is an element constituting a cation having an oxidation state of +4, +5 or 6 different from M, G is an element constituting a cation having an oxidation state of +3, K is a chalcogen element, x and y are real numbers greater than 0 independently of each other, and x is a real number greater than 0 and less than 3y. a, b, c, d are appropriately selected so as to form a stoichiometric number.
[0055] Specifically, it can be: the above-mentioned A contains one or more elements selected from lithium, sodium, and hydrogen, the above-mentioned M contains one or more elements selected from titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, tin, lead, antimony and bismuth, among which T contains one or more elements selected from silicon, germanium, phosphorus and arsenic, G contains one or more elements selected from boron, aluminum and gallium, and K contains one or more elements selected from oxygen and sulfur.
[0056] In a preferred embodiment of the present invention, A is lithium, M is tantalum, T is phosphorus, G is boron, and K is oxygen as constituent elements, and M is further contained as niobium.
[0057] The inventors of the present invention presume the specific structure of the monoclinic crystal as follows. The above-mentioned M and K anions are 6-coordinated to form a MK6 octahedral unit, and T and K are 4-coordinated to form a TK4 tetrahedral unit. In addition, some of the octahedral units of the MK6 are combined with two of the TK4 tetrahedral units in a manner of sharing vertices to form trimer connection units. At this time, in each trimer connection unit, the above-mentioned two TK4 tetrahedral units are combined with the first vertex of the vertices of the MK6 octahedral unit in a manner of sharing the K ion located at the second vertex facing the above-mentioned first vertex. Furthermore, the details of this structure are disclosed in the above-mentioned patent document 3.
[0058] The A ions are arranged in the space between the octahedral unit of MK6 and the tetrahedral unit of TK4. In addition, G exists in the form of oxide or sulfide at the grain boundary and partially replaces T of the tetrahedral unit of TK4. By including the constituent elements as described above including G, the predetermined a, b, c axis lengths and axis angle β are achieved. This chalcogenide can be prepared by the manufacturing method described later.
[0059] A chalcogenide containing a specific monoclinic crystal can provide a solid electrolyte having sufficient ion conductivity even when the firing temperature during production of the solid electrolyte is set to a low temperature (for example, 900° C. or lower).
[0060] In the present invention, the volume of the unit cell of the monoclinic crystal is preferably If it is within this range, it becomes a solid electrolyte with sufficient ion conductivity.
[0061] The content of monoclinic crystals in the solid electrolyte (= the amount of monoclinic crystals × 100 / the total amount of all confirmed crystals) is preferably 70.0% or more, more preferably 80.0% or more. The upper limit is not particularly limited, but is preferably less than 100.0%, more preferably less than 99.5%.
[0062] When the monoclinic crystal content of the present solid electrolyte is within the above range, the solid electrolyte tends to have high total ion conductivity.
[0063] Examples of compounds that may be contained in addition to the chalcogenides of (1) include LiPO3, Li3PO4, TaPO5, LiTa3O8, and LiTaO3. In addition, diffraction peaks derived from raw materials may be observed. Examples of raw materials include lithium carbonate (Li2CO3), tantalum pentoxide (Ta2O5), and boric acid.
[0064] The monoclinic crystal content in the solid electrolyte can be calculated by, for example, Rietveld analysis using the known analysis software RIETAN-FP (available from the homepage of Fujio Izumi, "RIETAN-FP·VENUS System Release File" (http: / / fujioizumi.verse.jp / download / download.html)).
[0065] A preferred embodiment of the solid electrolyte of the present invention is that the chalcogenide contains lithium, tantalum, boron, phosphorus and oxygen as constituent elements. In addition, the monoclinic crystal preferably contains lithium, tantalum, phosphorus and oxygen as constituent elements. In addition, boron is preferably contained in the grain boundary. If boron is contained in the grain boundary, it is easy to form a monoclinic shape, the overall ion conductivity becomes high, and the sintering temperature can be reduced.
[0066] In this case, from the viewpoint that the sintering temperature can be lowered when obtaining a solid electrolyte with sufficient ion conductivity, the boron content is preferably 0.10 atomic % or more, more preferably 0.50 atomic % or more. In addition, the upper limit is preferably 5.00 atomic % or less, more preferably 3.00 atomic % or less.
[0067] From the viewpoint of obtaining a solid electrolyte with higher lithium ion conductivity, the tantalum content is preferably 10.00 atomic % or more, more preferably 11.00 atomic % or more, and the upper limit is preferably 17.00 atomic % or less, more preferably 16.00 atomic % or less.
[0068] From the viewpoint of obtaining a solid electrolyte with higher lithium ion conductivity, the phosphorus content is preferably 5.00 atomic % or more, more preferably 6.00 atomic % or more, and the upper limit is preferably 8.50 atomic % or less, more preferably 8.00 atomic % or less.
[0069] From the viewpoint of obtaining a solid electrolyte with higher lithium ion conductivity, the lithium content is preferably 5.00 atomic % or more, more preferably 6.00 atomic % or more, and the upper limit is preferably 20.00 atomic % or less, more preferably 15.00 atomic % or less.
[0070] As a preferred embodiment, niobium is contained together with lithium, tantalum, boron, phosphorus and oxygen. When niobium is contained, the niobium content is preferably 0.10 atomic % or more, more preferably 0.50 atomic % or more, from the viewpoint of being able to lower the firing temperature when a sintered body with sufficient ion conductivity is obtained. The upper limit is 5.00 atomic % or less, more preferably 3.0 atomic % or less, further preferably 2.00 atomic % or less, and further preferably 1.60 atomic % or less.
[0071] In the present invention, when the chalcogenide contains silicon, the upper limit of the content thereof is preferably 0.15 atomic %. If the silicon content exceeds the upper limit, a solid electrolyte having sufficient ion conductivity may not be obtained.
[0072] The content of each element can be determined by a known method such as a high-frequency inductively coupled plasma (ICP) emission spectrometer or Auger electron spectroscopy (AES).
[0073] Chalcogenide can be produced by calcining raw material substances mixed in a stoichiometric ratio as shown in the above formula (1).
[0074] For example, the raw materials may be pulverized and mixed using a ball mill or a bead mill, and then sintered. In this case, the raw materials may be compressed into a predetermined shape and then sintered or sintered.
[0075] Alternatively, the obtained fired product may be mixed with various additives described below as necessary, pulverized, shaped by compression molding such as press molding, and fired or sintered to prepare a solid electrolyte.
[0076] As the raw material of A in the above formula (1), a carbonate, nitrate, borate or other salt of A can be used, as the raw material of M, an oxide, salt or other compound of M can be used, as the raw material of T, an oxide, salt of T can be used, and as the raw material of G, an oxide, salt of C can be used. Oxides also include hydroxides.
[0077] When the chalcogenide contains lithium, tantalum, boron, phosphorus and oxygen as constituent elements, for example, as a raw material of lithium, lithium carbonate, lithium oxide, lithium nitrate, lithium hydroxide, lithium acetate and hydrates thereof can be cited. Among them, lithium carbonate, lithium hydroxide and lithium acetate are preferred from the viewpoint of easy decomposition and reaction. In addition, a compound containing sodium or the like can be used as a raw material, and after calcination, sodium and lithium are ion-exchanged.
[0078] As the raw material material of tantalum, tantalum pentoxide and tantalum nitrate can be used.
[0079] As a raw material substance of phosphorus, phosphates are preferred. As phosphates, from the perspective of easy decomposition and reaction, for example, diammonium hydrogen phosphate, monoammonium dihydrogen phosphate, and ammonium phosphate can be cited.
[0080] As a raw material substance of boron, boric acid, boron oxide, etc. can also be used.
[0081] In addition, as a raw material substance, a salt containing two or more elements constituting the solid electrolyte can also be used. For example, LiPO3, LiH2PO4, LiBO2, LiB3O5, Li2B4O7, Li3B 11 O 18 、Li3BO3、Li3B7O 12 、Li4B2O5、Li6B4O9、Li 3-x B 1-x C x O3(0 < x < 1), Li 4-x B 2-x C x O5(0 < x < 2), etc. can be used.
[0082] Furthermore, as a compound containing a niobium atom, for example, an oxide or a salt can be cited. For example, Nb2O5, LiNbO3, LiNb3O8, NbPO5 can be used.
[0083] These raw materials can be used individually or in combination of two or more.
[0084] The firing varies depending on the firing time and is heated at a temperature of 500 to 1200 °C, preferably 700 to 1000 °C, for about 1 to 16 hours. Thereby, impurity components contained in the raw materials are volatilized and removed to obtain the target electrolyte.
[0085] Sintering of the compression-molded compact is carried out by heating in the temperature range of 600 to 1200 °C for about 1 to 96 hours.
[0086] The above-mentioned firing and sintering can be carried out in the atmosphere, but can also be carried out in an atmosphere of nitrogen and / or argon whose oxygen content is adjusted in the range of 0 to 20 vol%, or in a reducing gas atmosphere such as a nitrogen-hydrogen mixed gas containing a reducing gas such as hydrogen. As the reducing gas, in addition to hydrogen, ammonia gas, carbon monoxide gas, etc. can also be used.
[0087] 《All-Solid-State Battery》
[0088] The all-solid-state battery of the present invention includes a positive electrode having a positive electrode active material, a negative electrode having a negative electrode active material, and a solid electrolyte layer located between the positive electrode and the negative electrode, and the solid electrolyte layer contains the above-mentioned lithium ion conductive solid electrolyte.
[0089] <Solid Electrolyte Layer>
[0090] The solid electrolyte may be used alone or in combination of two or more. When two or more solid electrolytes are used, two or more solid electrolytes may be mixed, or two or more solid electrolyte layers may be formed to form a multilayer structure.
[0091] The solid electrolyte layer is not particularly limited as long as it contains the solid electrolyte of the present invention, and its content is, for example, 50% by mass or more, can be in the range of 60% by mass or more and 100% by mass or less, can be in the range of 70% by mass or more and 100% by mass or less, and can be 100% by mass. It is preferably composed of the above-mentioned solid electrolyte.
[0092] Furthermore, it is preferred that the positive electrode active material layer and the negative electrode active material layer contain the above-mentioned solid electrolyte. By setting it in this way, it is possible to improve the ion conductivity by improving the adhesion between the solid electrolyte layer-positive electrode active material layer and the solid electrolyte layer-negative electrode active material layer, which is preferred.
[0093] From the viewpoints of embodying plasticity, a binder may also be contained in the solid electrolyte layer. As such a binder, acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. may be exemplified. However, in order to easily achieve high output, from the viewpoints of preventing excessive coagulation of the solid electrolyte and being able to form a solid electrolyte layer with a uniformly dispersed solid electrolyte, the binder contained in the solid electrolyte layer is preferably less than 5% by mass.
[0094] The thickness of the solid electrolyte layer is not particularly limited, but is usually 0.1 μm or more and 1 mm or less.
[0095] As a method for forming a solid electrolyte layer, as described above, there can be cited a method of press-forming a powder of a solid electrolyte material containing a solid electrolyte and other components added as needed, etc. When the powder of the solid electrolyte material is press-formed, a pressing pressure of 1 MPa or more and 600 MPa or less is usually applied.
[0096] An all-solid-state battery according to one embodiment of the present invention (hereinafter also referred to as "the present battery") comprises: a positive electrode having a positive electrode active material, a negative electrode having a negative electrode active material, and a solid electrolyte layer located between the positive electrode and the negative electrode, wherein the solid electrolyte layer contains the present solid electrolyte.
[0097] The battery may be a primary battery or a secondary battery, but is preferably a secondary battery, and more preferably a lithium ion secondary battery, from the viewpoint of further exerting the effects of the present invention.
[0098] The structure of the battery is not particularly limited as long as it includes a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, and may be any of a so-called thin film type, a stacked type, and a bulk type.
[0099] <Positive electrode>
[0100] The positive electrode is not particularly limited as long as it has a positive electrode active material, but preferably, a positive electrode having a positive electrode collector and a positive electrode active material layer is used.
[0101] [Positive electrode active material layer]
[0102] The positive electrode active material layer may contain a solid electrolyte, a conductive material, a binder, and the like as optional components.
[0103] There is no particular restriction on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. The positive electrode active material may contain lithium or may not contain lithium.
[0104] The thickness of the positive electrode active material layer may be appropriately selected according to the battery structure to be formed, and is not particularly limited, but may be 30 nm to 5000 nm.
[0105] Positive active material
[0106] The positive electrode active material preferably contains an element selected from LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1 and 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiCoO2, LiNiO2, LiMn2O4, Li2CoP2O7, Li3V2(PO4)3, Li3Fe2(PO4)3, LiNi 0.5 Mn 1.5 O4 and Li4Ti5O12 One or more compounds.
[0107] A coating layer containing a Li ion conductive oxide may also be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte.
[0108] Examples of Li ion conductive oxides include LiNbO3, Li4Ti5O 12 and Li3PO4, etc. The thickness of the coating is, for example, greater than 0.1 nm, or greater than 1 nm. On the other hand, the thickness of the coating is, for example, less than 100 nm, or less than 20 nm. The coverage of the coating on the surface of the positive electrode active material is, for example, greater than 70%, or greater than 90%.
[0109] The content of the solid electrolyte in the positive electrode layer is not particularly limited, and can be, for example, in the range of 1 to 80 mass % when the total mass of the positive electrode layer is 100 mass %.
[0110] Solid electrolyte
[0111] The solid electrolyte contained in the positive electrode active material layer may be the solid electrolyte of the present invention, and examples thereof include oxide-based solid electrolytes and sulfide-based solid electrolytes described below other than the solid electrolyte of the present invention.
[0112] Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5, and Li3PS4, etc. "X" represents a halogen element.
[0113] Examples of the oxide-based solid electrolyte include Li 6.25 La3Zr2Al 0.25 O 12 , Li3PO4 and Li 3+x PO 4-x N x (1≤x≤3) etc.
[0114] From the viewpoint of good handling properties, the solid electrolyte is preferably in the form of particles. The volume average particle size (D 50 ) is not particularly limited, but the lower limit is preferably 0.5 μm or more, and the upper limit is preferably 2 μm or less.
[0115] As the conductive material, known materials can be used, for example, carbon materials and metal particles can be cited. As the carbon material, for example, at least one selected from carbon black such as acetylene black and furnace black, carbon nanotubes and carbon nanofibers can be cited, wherein, from the viewpoint of electronic conductivity, at least one selected from carbon nanotubes and carbon nanofibers is preferably selected. The carbon nanotubes and carbon nanofibers can also be VGCF (vapor-grown carbon fiber). As metal particles, particles such as Ni, Cu, Fe and SUS can be cited. The content of the conductive material in the positive electrode active material layer is not particularly limited.
[0116] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode active material layer is not particularly limited.
[0117] The thickness of the positive electrode active material layer is not particularly limited.
[0118] The positive electrode active material layer can be formed by a conventionally known method.
[0119] For example, a positive electrode active material and other components added as needed are placed in a solvent and stirred to prepare a slurry for a positive electrode active material layer, and the slurry for a positive electrode active material layer is applied to one side of a support such as a positive electrode current collector and dried to obtain a positive electrode active material layer.
[0120] Examples of the solvent include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone.
[0121] The method for coating the positive electrode active material layer slurry on one side of a support such as a positive electrode current collector is not particularly limited, and examples thereof include doctor blade method, metal mask printing method, electrostatic coating method, dip coating method, spraying method, roll coating method, gravure coating method and screen printing method.
[0122] As the support, any self-supporting material may be appropriately selected and used without particular limitation, and for example, metal foils such as Cu and Al may be used.
[0123] In addition, as another method for forming the positive electrode active material layer, the positive electrode active material layer can also be formed by press-forming the powder of the positive electrode mixture containing the positive electrode active material and other components added as needed. When the powder of the positive electrode mixture is press-formed, a pressing pressure of more than 1 MPa and less than 600 MPa is usually loaded.
[0124] The pressurizing method is not particularly limited, and examples thereof include a method of applying pressure using a plate press, a roll press, and the like.
[0125] As the positive electrode current collector, a known metal that can be used as a current collector of an all-solid battery can be used. As such a metal, a metal material containing one or more elements selected from Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge and In can be exemplified.
[0126] The form of the positive electrode current collector is not particularly limited, and may be in various forms such as a foil and a mesh.
[0127] The shape of the positive electrode as a whole is not particularly limited, and may be in a sheet shape. In this case, the thickness of the positive electrode as a whole is not particularly limited, and may be appropriately determined according to the target performance.
[0128] The content of the positive electrode active material in the positive electrode active material layer is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.
[0129] When the content of the positive electrode active material is within the above range, the positive electrode active material functions well, and there is a tendency that a battery having a high energy density can be easily obtained.
[0130] ·additive
[0131] Preferred examples of the conductive additive include metal materials such as Ag, Au, Pd, Pt, Cu, and Sn, and carbon materials such as acetylene black, Ketjen black, carbon nanotubes, and carbon nanofibers.
[0132] As the sintering aid, the same compounds as the compound (b), compounds containing a niobium atom, compounds containing a bismuth atom, and compounds containing a silicon atom are preferred.
[0133] The additives used in the positive electrode active material layer may be one kind or two or more kinds.
[0134] Positive electrode collector
[0135] The positive electrode current collector is not particularly limited as long as its material is a material that conducts electrons without electrochemical reaction. As the material of the positive electrode current collector, for example, conductive metal oxides such as single substances of metals such as copper, aluminum, and iron, alloys containing these metals, antimony-doped tin oxide (ATO), and tin-doped indium oxide (ITO) can be cited.
[0136] Furthermore, as the positive electrode current collector, a current collector having a conductive adhesive layer provided on the surface of the conductor may be used. Examples of the conductive adhesive layer include a layer containing a granular conductive material or a fibrous conductive material.
[0137] <Negative electrode>
[0138] The negative electrode is not particularly limited as long as it has a negative electrode active material, and preferably, there is used a negative electrode having a negative electrode collector and a negative electrode active material layer.
[0139] [Negative Electrode Active Material Layer]
[0140] The negative electrode active material layer is not particularly limited as long as it contains a negative electrode active material, but preferably contains a negative electrode active material and a solid electrolyte, and may further contain additives such as a conductive aid and a sintering aid.
[0141] The thickness of the negative electrode active material layer is not particularly limited, and may be 30 nm or more and 5000 nm or less.
[0142] Negative electrode active material
[0143] As the negative electrode active material, for example, a known material can be used, and specifically, it is preferably selected from LiM3PO4 [M3 is one or more elements selected from Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O], LiM5VO4 [M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti], Li2M6P2O7 [M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements of V and O], LiVP2O7, Li x7 V y7 M7 z7 [2≤x7≤4, 1≤y7≤3, 0≤z7≤1 and 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr], Li 1+x8 Al x8 M8 2-x8 (PO4)3[0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge], (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 )O4[M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0 and 0≤y9≤0.6, a9 is the average valence of M9, b9 is the average valence of M10], LiNb2O7, Li4Ti5O 12 、Li4Ti5PO 12 , TiO2, LiSi and graphite.
[0144] The negative electrode active material content in the negative electrode active material layer is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.
[0145] When the content of the negative electrode active material is within the above range, the negative electrode active material functions well, and there is a tendency that a battery with high energy density can be easily obtained.
[0146] The negative electrode active material layer may contain a solid electrolyte. Examples of the solid electrolyte include known solid electrolytes including the solid electrolyte of the present invention.
[0147] The negative electrode current collector may be a material that does not alloy with Li, for example, SUS, copper, and nickel. As the form of the negative electrode current collector, for example, foil and plate can be mentioned. The top view shape of the negative electrode current collector is not particularly limited, for example, a circle, an ellipse, a rectangle, and any polygon can be mentioned. In addition, the thickness of the negative electrode current collector varies depending on the shape, for example, it can be in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0148] The negative electrode active material layer can be formed by a conventionally known method.
[0149] The all-solid-state battery includes an outer casing that accommodates a positive electrode, a negative electrode, and a solid electrolyte layer as necessary.
[0150] The material of the outer casing is not particularly limited as long as it is stable to the electrolyte, and examples thereof include resins such as polypropylene, polyethylene, and acrylic resin.
[0151] The all-solid-state battery may be an all-solid-state lithium secondary battery.
[0152] Examples of the shape of the all-solid-state battery include a button type, a laminate type, a cylindrical type, and a square type.
[0153] The method for producing the all-solid-state battery is not particularly limited, and the above-mentioned layers may be stacked and compressed under pressure as necessary.
[0154] Example
[0155] Hereinafter, the present invention will be specifically described based on examples. However, the present invention is not limited to these examples.
[0156] [Example 1]
[0157] Lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, Merck & Co., Ltd., purity 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%), boric acid (H3BO3) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.5% or more) and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, Merck & Co., Ltd., purity 98% or more) were weighed so that the atomic ratio of lithium, tantalum, boron and phosphorus (Li:Ta:B:P) satisfied the stoichiometric formula of Table 1. Furthermore, lithium carbonate was weighed so that the amount of lithium atoms in Table 1 became 1.05 times the amount of lithium atoms in Table 1, and diammonium hydrogen phosphate was weighed so that the amount of phosphorus atoms in Table 1 became 1.06 times the amount in Table 1 in order to suppress the generation of by-products in the calcination process. An appropriate amount of toluene was added to each weighed raw material powder, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: 5 mm in diameter) to obtain a primary mixture.
[0158] The obtained primary mixture was placed in an alumina dish and heated to 1000°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by MOTOYAMA Co., Ltd.), and sintered at this temperature for 4 hours to obtain a primary sintered product.
[0159] An appropriate amount of toluene was added to the obtained primary fired product, and the mixture was pulverized and mixed for 2 hours using a zirconia ball mill (zirconia balls: 1 mm in diameter) to obtain a secondary mixture.
[0160] The secondary mixture was subjected to a pressure of 40 MPa by a hydraulic press using a tablet forming machine to form a disc-shaped body having a diameter of 10 mm and a thickness of 1 mm. The disc-shaped body was then subjected to a pressure of 300 MPa by CIP (cold isostatic pressing) to produce pellets.
[0161] The obtained pellets were placed in an alumina dish and heated to 850°C at a heating rate of 10°C / min in an atmosphere of air (flow rate: 100 mL / min) using a rotary sintering furnace (manufactured by MOTOYAMA Co., Ltd.), and sintered at this temperature for 96 hours to obtain a sintered body.
[0162] The obtained sintered body was cooled to room temperature, taken out from the rotary sintering furnace, and stored in a dehumidified nitrogen atmosphere to obtain a solid electrolyte.
[0163] [Examples 2 to 4]
[0164] A solid electrolyte was prepared in the same manner as in Example 1 except that the mixing ratio of the raw materials was changed so that the atomic ratio of lithium, tantalum, boron, and phosphorus satisfied the stoichiometric formula in Table 1.
[0165] [Examples 5 and 6]
[0166] In Example 1, niobium pentoxide (Nb2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%) is also used, and the raw material powders are used in a manner such that the atomic ratio of lithium, tantalum, niobium, boron and phosphorus (Li:Ta:Nb:B:P) satisfies the stoichiometric formula in Table 1. Except for this, the solid electrolyte is prepared in the same manner as in Example 1.
[0167] [Example 7]
[0168] In Example 1, silicon dioxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%) is also used, and the raw material powders are used in a manner such that the atomic ratio of lithium, tantalum, boron, phosphorus and silicon (Li:Ta:B:P:Si) satisfies the stoichiometric formula in Table 1. Except for this, the solid electrolyte is prepared in the same manner as in Example 1.
[0169] [Comparative Example 1]
[0170] For lithium carbonate (Li2CO3) (manufactured by Sigma-Aldrich, Merck, with a purity of 99.0% or more), tantalum pentoxide (Ta2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., with a purity of 99.9%) and diammonium hydrogen phosphate ((NH4)2HPO4) (manufactured by Sigma-Aldrich, Merck, with a purity of 98% or more), each raw material powder is used in a manner such that the atomic ratio of lithium, tantalum and phosphorus (Li:Ta:P) satisfies the stoichiometric formula in Table 1, and the solid electrolyte is prepared in the same manner as in Example 1.
[0171] [Comparative Example 2]
[0172] Silicon dioxide (SiO2) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%) was also used, and the raw material powders were used in a manner such that the atomic ratio of lithium, tantalum, phosphorus and silicon (Li:Ta:P:Si) satisfied the stoichiometric formula in Table 1. The solid electrolyte was prepared in the same manner as in Comparative Example 1, except that the above-mentioned methods were used.
[0173] [Comparative Example 3]
[0174] Niobium pentoxide (Nb2O5) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%) was also used, and the raw material powders were used in a manner such that the atomic ratio of lithium, tantalum, niobium and phosphorus (Li:Ta:Nb:P) satisfied the stoichiometric formula in Table 1. The solid electrolyte was prepared in the same manner as in Comparative Example 1, except that the above was not done.
[0175] [Comparative Example 4]
[0176] Weigh lithium carbonate (Li₂CO₃, manufactured by Merck Sigma - Aldrich, purity 99.0% or more), tantalum pentoxide (Ta₂O₅, manufactured by Fujifilm Wako Pure Chemical Corporation, purity 99.9%), and diammonium hydrogen phosphate ((NH₄)₂HPO₄, manufactured by Merck Sigma - Aldrich, purity 98% or more) in such a way that the atomic ratio of lithium, tantalum, and phosphorus (Li:Ta:P) satisfies 1.05:2.00:1.06. Add an appropriate amount of toluene to the weighed raw material powders, and use a zirconia ball mill (zirconia balls: diameter 5 mm) to crush and mix for 2 hours to obtain a primary mixture.
[0177] Put the obtained primary mixture into an alumina dish, and use a rotary firing furnace (manufactured by MOTOYAMA Co., Ltd.). Under the atmosphere of air (flow rate: 100 mL / minute), heat it to 1000 °C at a heating rate of 10 °C / minute, and carry out firing at this temperature for 4 hours to obtain a primary fired product.
[0178] Weigh the obtained primary fired product and Li₄B₂O₅ obtained by a known manufacturing method in such a way that the molar ratio becomes 0.85:0.15. Use an agate mortar to crush and mix the weighed powders for 30 minutes to obtain a secondary mixture.
[0179] Use a tablet press to apply a pressure of 40 MPa to the obtained secondary mixture with a hydraulic press to form a disk - shaped compact with a diameter of 10 mm and a thickness of 1 mm. Then, apply a pressure of 300 MPa to the disk - shaped compact by CIP (cold isostatic pressing) to produce pellets.
[0180] Put the obtained pellets into an alumina dish, and use a rotary firing furnace (manufactured by MOTOYAMA Co., Ltd.). Under the atmosphere of air (flow rate: 100 mL / minute), heat it to 850 °C at a heating rate of 10 °C / minute, and carry out firing at this temperature for 96 hours to obtain a sintered body.
[0181] After cooling the obtained sintered body to room temperature, take it out from the rotary firing furnace and transfer it to be stored under a dehumidified nitrogen atmosphere to obtain a solid electrolyte.
[0182] <X - ray diffraction (XRD)>
[0183] Use an agate mortar to crush the obtained solid electrolyte for 30 minutes to obtain a powder for XRD measurement.
[0184] The powder for XRD measurement was subjected to X-ray diffraction measurement using a powder X-ray diffraction measuring apparatus PANalytical MPD (manufactured by Spectris Corporation) (Cu-Kα rays (output power: 45 kV and 40 mA), diffraction angle 2θ=10 to 50°, step width: 0.013°, incident side collimator: 0.04 rad, incident side anti-scatter slit: 2°, light-receiving side collimator: 0.04 rad, light-receiving side anti-scatter slit: 5 mm) to obtain an X-ray diffraction (XRD) pattern. The obtained XRD pattern was subjected to Rietveld analysis using the known analysis software RIETAN-FP (available from the homepage of Fujio Izumi, "RIETAN-FP·VENUS System Release File" (http: / / fujioizumi.verse.jp / download / download.html)), to confirm the contained crystal structure, and the a, b, c axis lengths, axis angle β, unit cell volume V and content of the monoclinic crystal were calculated. The calculated a, b, c axis lengths, axis angle β, unit cell volume V and content of the monoclinic crystal are collectively recorded in Table 1.
[0185] The XRD patterns of the solid electrolytes obtained in Example 3 and Comparative Example 1 are shown in Figure 1 .
[0186] Depend on Figure 1 It can be seen that only the peak derived from the monoclinic crystal structure of LiTa2PO8 is observed in Comparative Example 1. In the solid electrolyte obtained in Example 3, in addition to the peak derived from the LiTa2PO8 structure, the peak derived from LiTa3O8 (ICSD code: 493) and the peak derived from Ta2O5 (ICSD code: 66366) are also observed.
[0187] In each XRD pattern of the solid electrolyte obtained in the embodiment, the same diffraction pattern as the XRD pattern of the solid electrolyte of Comparative Example 1 was confirmed, but the a, b, c axis lengths of the monoclinic crystal and the volume V of the unit cell calculated by Rietveld analysis were smaller than those of the comparative example. In the present solid electrolyte, boron atoms are considered to be contained in the lattice of the monoclinic crystal structure composed of lithium, tantalum, phosphorus and oxygen as constituent elements.
[0188] In each XRD pattern of the solid electrolyte obtained in Comparative Example 4, the same diffraction pattern as the XRD pattern of the solid electrolyte in Comparative Example 1 was confirmed, and the a, b, c axis lengths of the monoclinic crystal and the unit cell volume V calculated by Rietveld analysis were at the same level as those in Comparative Example 1. In the present solid electrolyte, it is believed that no boron atoms are contained in the lattice of the monoclinic crystal structure composed of lithium, tantalum, phosphorus and oxygen as constituent elements.
[0189] <Electron Probe Microanalyzer (EPMA)>
[0190] The obtained solid electrolyte was cut, and the cross section was exposed by ion milling (CP processing, acceleration voltage: 6 kV, processing time: 8 hours).
[0191] The cross-sectional EPMA measurement of the obtained solid electrolyte was performed using an EPMA apparatus JMX-8530F (manufactured by JEOL Ltd.) (accelerating voltage: 10 kV, irradiation current: 1×10 -7 A), obtain secondary electron image and boron mapping image.
[0192] Figure 2 The secondary electron image and boron mapping image obtained by EPMA of the solid electrolyte obtained in Example 3 are shown. In the secondary electron image, the portion corresponding to the gray intermediate color is monoclinic, and the black and white portions represent grain boundaries. In the boron mapping, the portion with a high boron atom content is represented by white, and the portion with a low boron atom content is represented by black.
[0193] Depend on Figure 2 It can be seen that most of the boron atoms exist at the grain boundaries.
[0194] <Total Conductivity>
[0195] A gold layer was formed on both surfaces of the obtained solid electrolyte using a sputtering machine, thereby obtaining a measurement pellet for evaluating ion conductivity.
[0196] Before the measurement, the obtained test pellets were kept in a constant temperature bath at 25°C for 2 hours. Next, at 25°C, an impedance analyzer (Solartron Analytical, model: 1260A) was used to perform AC impedance measurement in the range of 1 Hz to 10 MHz at an amplitude of 25 mV. The equivalent circuit analysis software ZView attached to the device was used to fit the obtained impedance spectrum with an equivalent circuit to obtain the lithium ion conductivity in the grains and in the grain boundaries, and the total ion conductivity was calculated by summing them. The results are shown in Table 1.
[0197]
[0198] As can be seen from Table 1, the lithium ion conductive solid electrolyte of the present invention is excellent in ion conductivity.
Claims
1. A lithium ion conductive solid electrolyte comprising a chalcogenide, The chalcogenide has a monoclinic crystal structure, and The a-axis length of the monoclinic crystal is The length of the b axis is The length of the c-axis is and the axis angle β is in the range of 90.01 to 90.08°, The chalcogenide has the following stoichiometric formula (1): A x (M a T b G c K d ) y (1) In the general formula (1), A is one or more elements selected from lithium, sodium, and hydrogen, M is one or more elements selected from titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, tin, lead, antimony, and bismuth, T is one or more elements selected from silicon, germanium, phosphorus, and arsenic, G is one or more elements selected from boron, aluminum, and gallium, K is one or more elements selected from oxygen and sulfur, x and y are independent real numbers greater than 0, x is a real number greater than 0 and less than 3y, a, b, c, d are stoichiometric numbers, The content of the monoclinic crystal in the solid electrolyte, that is, the amount of monoclinic crystals × 100 / the total amount of all confirmed crystals, is 70.0% or more and less than 100.0%. 2 . The lithium ion conductive solid electrolyte according to claim 1 , wherein the chalcogenide has lithium, tantalum, boron, phosphorus and oxygen as constituent elements. 3 . The lithium ion conductive solid electrolyte according to claim 1 , wherein the monoclinic crystal structure is composed of lithium, tantalum, phosphorus and oxygen as constituent elements.
4. The lithium ion conductive solid electrolyte according to any one of claims 1 to 3, wherein the unit cell volume of the monoclinic crystal is 5. The lithium ion conductive solid electrolyte according to claim 2 or 3, wherein the content of boron is 0.10 to 5.00 atomic %.
6. The lithium ion conductive solid electrolyte according to claim 2 or 3, wherein the content of tantalum is 10.00 to 17.00 atomic %.
7. The lithium ion conductive solid electrolyte according to claim 2 or 3, wherein the phosphorus content is 5.00 to 8.50 atomic %.
8. The lithium ion conductive solid electrolyte according to claim 2 or 3, wherein the lithium content is 5.00 to 20.00 atomic %.
9. The lithium ion conductive solid electrolyte according to claim 2 or 3, further comprising niobium, wherein the content of niobium is 0.10 to 5.00 atomic %. 10 . The lithium ion conductive solid electrolyte according to claim 1 , further comprising silicon, wherein the upper limit of the silicon content is 0.15 atomic %. 11 . The lithium ion conductive solid electrolyte according to claim 2 , wherein boron is present in the grain boundaries.
12. An all-solid-state battery, comprising: A positive electrode having a positive active material, A negative electrode having a negative electrode active material, and A solid electrolyte layer between the positive electrode and the negative electrode, The solid electrolyte layer includes the lithium ion conductive solid electrolyte according to any one of claims 1 to 11.
13. The all-solid-state battery according to claim 12, wherein the positive electrode active material contains a compound selected from LiM3PO 4 、LiM5VO 4 , Li 2 M6P 2 O 7 、LiVP 2 O 7 , Li x7 V y7 M7 z7 , Li 1+x8 Al x8 M8 2-x8 (PO 4 ) 3 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiCoO 2 、LiNiO 2 、LiMn 2 O 4 , Li 2 CoP 2 O 7 , Li 3 V 2 (PO 4 ) 3 , Li 3 Fe 2 (PO 4 ) 3 、LiNi 0.5 Mn 1.5 O 4 and Li 4 Ti 5 O 12 One or more compounds, LiM3PO 4 wherein M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O, LiM5V 4 wherein M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti, Li 2 M6P 2 O 7 wherein M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O, Li x7 V y7 M7 z7 , 2≤x7≤4, 1≤y7≤3, 0≤z7≤1 and 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr, Li 1+x8 Al x8 M8 2-x8 (PO 4 ) 3 0≤x8≤0.8, and M8 is one or more elements selected from Ti and Ge.
14. The all-solid-state battery according to claim 12 or 13, wherein the negative electrode active material contains a compound selected from LiM3PO 4 、LiM5VO 4 , Li 2 M6P 2 O 7 、LiVP 2 O 7 , Li x7 V y7 M7 z7 , Li 1+x8 Al x8 M8 2-x8 (PO 4 ) 3 、(Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1- y9 M10 y9 ) 4 、LiNb 2 O 7 , Li 4 Ti 5 O 12 , Li 4 Ti 5 PO 12 、TiO 2 , LiSi and graphite, LiM3PO 4 wherein M3 is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, Ti and V, or two elements of V and O, LiM5V 4 wherein M5 is one or more elements selected from Fe, Mn, Co, Ni, Al and Ti, Li 2 M6P 2 O 7 wherein M6 is one or more elements selected from Fe, Mn, Co, Ni, Al, Ti and V, or two elements V and O, Li x7 V y7 M7 z7 , 2≤x7≤4, 1≤y7≤3, 0≤z7≤1 and 1≤y7+z7≤3, M7 is one or more elements selected from Ti, Ge, Al, Ga and Zr, Li 1+x8 Al x8 M8 2-x8 (PO 4 ) 3 , 0≤x8≤0.8, M8 is one or more elements selected from Ti and Ge, (Li 3-a9x9+(5-b9)y9 M9 x9 )(V 1-y9 M10 y9 ) 4 In the formula (A), M9 is one or more elements selected from Mg, Al, Ga and Zn, M10 is one or more elements selected from Zn, Al, Ga, Si, Ge, P and Ti, 0≤x9≤1.0 and 0≤y9≤0.6, a9 is the average valence of M9, and b9 is the average valence of M10. 15 . The all-solid-state battery according to claim 12 , wherein the positive electrode and the negative electrode contain the lithium ion conductive solid electrolyte according to claim 1 . 16 . The all-solid-state battery according to claim 13 , wherein the positive electrode and the negative electrode contain the lithium ion conductive solid electrolyte according to claim 1 . 17 . The all-solid-state battery according to claim 14 , wherein the positive electrode and the negative electrode contain the lithium ion conductive solid electrolyte according to claim 1 .
Citation Information
Patent Citations
Sulfide solid electrolyte, manufacturing method of sulfide solid electrolyte, electrode body, and all-solid-state battery
JP2020173992A
Solid electrolyte and all-solid battery
WO2019044901A1
Ion-conductive solid electrolyte compound, method for preparing same, and electrochemical device comprising same
WO2020036290A1
Lithium ion battery and method for producing lithium ion battery
CN107768722A
Solid electrolyte, electrode mix, solid electrolyte layer, and all-solid-state battery
CN112106230A
